Developing of Four-Tier Diganostic Test to Identify Test Profile on Acid and Base Materials - Lukman, Isna Rezkia; Unaida, Ratna; Fakhrah, Fakhrah (Universitas Muhammadiyah Mataram, 2022)
Misconceptions that occur continuously and protracted can interfere with the learning process. Therefore, educators must be able to identify precisely the misconceptions that occur. This research was conducted to find out the implementation of four-tier diagnostic tests in analyzing the misconceptions of students in high school in North Aceh regency and understand the results of analysis of the comprehension level of learners' concepts, whether they Scientific conception, Lack of knowledge, and misconception. Four-tier diagnostic test instrument has been developed by adapting 4D models (Define, Design, Development and Disseminate). Through these steps, the four-tier diagnostic test instrument is produced that is valid through content validation with content-validity coefficient of 0.89 and an average aspect of 4.5 and includes an excellent category. On average, the overall profile of learners got 44.47% who Scientific conception, 44.03% Lack of knowledge and 11.50% who experienced misconceptions in acids and bases materials. The implication of this study is that educators can analyze scientific conception, lack of knowledge and misconceptions on acids and bases materials in learners, and use suitable learning methods so that the misconception is not repeated.